A comparison of the Enk Fiberoptic Atomizer Set™ with boluses of topical anaesthesia for awake fibreoptic intubation1. (6th May 2016) - Pirlich, N.; Lohse, J. A.; Schmidtmann, I.; Didion, N.; Piepho, T.; Noppens, R. R.
Summary: We compared the Enk Fiberoptic Atomizer Set ™ with boluses of topical anaesthesia administered via the working channel during awake fibreoptic tracheal intubation in 96 patients undergoing elective surgery. Patients who received topical anaesthesia via the atomiser, compared with boluses via the fibreoptic scope, reported a better median (IQR [range]) level of comfort: 1 (1–3 [1–10]) vs. 4 (2–6 [1–10]), p < 0.0001; experienced a reduced total number of coughs: 6 (3–10 [0–34]) vs. 11 (6–13 [0–25]), p = 0.0055; and fewer distinct coughing episodes: 7% vs. 27% respectively, p = 0.0133. The atomiser technique was quicker: 5 (3–6 [2–12]) min vs. 6 (5–7 [2–15]) min, p = 0.0009; and required less topical lidocaine: 100 mg (100–100 [80–160]) vs. 200 mg (200–200 [200–200]), p < 0.0001. Four weeks after nasal intubation, the incidence of nasal pain was less in the atomiser group compared with the control group (8% vs. 50%, p = 0.0015). We conclude that the atomiser was superior to bolus application for awake fibreoptic tracheal intubation.